Nasogastric Drip Rehydration Therapy in Acute Diarrhea with Severe Dehydration - Syamsul Hidayat; Srie Enggar K. D.; Nancy Pardede; Rusdi Ismail (Indonesian Pediatric Society, 1988)
WHO recommended severe dehydration without shock in acute diarrhea to be rehydrated by nasogastric drips (NGD) of oral rehydration solution (oralit). In this respect the criteria of a still palpable and countable pulse, the absence of meteorism and absence of complication, the reverse warranting iv fluid therapy, can be used as practical guidelines to identify the patient